Individual-level factors associated with variation in mycobacterial-specific immune response: Gender and previous BCG vaccination status. (January 2016) - Rhodes, Sophie J.; Knight, Gwenan M.; Fielding, Katherine; Scriba, Thomas J.; Pathan, Ansar A.; McShane, Helen; Fletcher, Helen; White, Richard G.
Summary: Introduction: A more effective tuberculosis (TB) vaccine is needed to eliminate TB disease. Many new vaccine candidates enhance the immunogenicity of the existing vaccine, Bacillus Calmette–Guérin (BCG). Understanding BCG induced immune variation is key to developing a new vaccine. Aims: We aimed to establish if individual-level covariates were associated with cell-mediated immune response (interferon gamma (IFN-γ)) at vaccine trial enrolment (baseline) in a long-term retrospective analysis (LTR) and after BCG vaccination in a short-term prospective analysis (STP). Methods: Four covariates were analysed: gender, country, BCG vaccination history and monocyte/lymphocyte cell count ratio. Univariable and multivariable linear regression were conducted on IFN-γ response at baseline for LTR, and area under the curve (AUC), 24 week and peak IFN-γ response for STP. Results: Previous BCG vaccination was strongly associated with higher IFN-γ response at baseline (LTR analysis) ( p -values < 0.05). Being male showed a weak association with higher baseline response ( p -value = 0.1). BCG revaccination was strongly associated with a larger response increase than primary-vaccination (AUC & peak p -values < 0.01), but did not differ at 24 weeks (STP analysis). All other covariates were non-significant ( p -values > 0.1). Conclusion: This analysis suggests that previous BCG vaccination and gender are associated with durable IFN-γ responses. Vaccine trials may need to stratify by BCG vaccination history and gender.